2013
DOI: 10.1007/s11010-013-1887-0
|View full text |Cite
|
Sign up to set email alerts
|

Chemopreventive effects of resveratrol in a rat model of cerulein-induced acute pancreatitis

Abstract: In the past decades, a greater understanding of acute pancreatitis has led to improvement in mortality rates. Nevertheless, this disease continues to be a health care system problem due to its economical costs. Future strategies such as antioxidant supplementation could be very promising, regarding to beginning and progression of the disease. For this reason, this study was aimed at assessing the effect of exogenous administration of resveratrol during the induction process of acute pancreatitis caused by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…Pancreatic GSH depletion has been shown in the initial phase of acute pancreatitis. 8,11,37,38 However, while some reports have shown increased pancreatic GSSG in AP, 13,14,[37][38][39] others have found that pancreatic GSSG levels and the GSSG/GSH ratio remains essentially unchanged during the early course of AP. 10,12,14,39 Rau et al 12 demonstrated a significant decrease of GSH levels parallel with an increased ratio of GSSG/Total glutathione.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Pancreatic GSH depletion has been shown in the initial phase of acute pancreatitis. 8,11,37,38 However, while some reports have shown increased pancreatic GSSG in AP, 13,14,[37][38][39] others have found that pancreatic GSSG levels and the GSSG/GSH ratio remains essentially unchanged during the early course of AP. 10,12,14,39 Rau et al 12 demonstrated a significant decrease of GSH levels parallel with an increased ratio of GSSG/Total glutathione.…”
mentioning
confidence: 99%
“…4,[6][7][8][9][10] Previous studies have confirmed the participation of ROS at early stages of AP, regardless of the underlying cause. [11][12][13] The characteristics of the pancreatitis induced by cerulein (a decapeptide and cholecystokinin analogue) resemble the early phase of AP in humans.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Evidences support that resveratrol plays a pivotal role in cell physiology protection. Namely, it activates cell defense pathways or it inhibits mechanisms underlying disease, leading then to protection and cell survival in different tissues (Carrasco et al 2014;Faghihzadeh et al 2014;Jha et al 2012;Joe et al 2015;Liu et al 2014;Rouse et al 2014;Sin et al 2015;Wang et al 2014 . Fura-2 has been described as a dye with a high selectivity for Ca 2?…”
Section: Introductionmentioning
confidence: 99%